1975
DOI: 10.1136/bmj.2.5968.424-a
|View full text |Cite
|
Sign up to set email alerts
|

Running and primary osteoarthritis of the hip.

Abstract: ST-T wave changes would be difficult to explain without specific myocardial involvement; probably, therefore, these were manifestations of Q-fever myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
2

Year Published

1981
1981
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 2 publications
1
62
0
2
Order By: Relevance
“…Prolonged exposure to higher levels of recreational physical activity has been reported to have a statistically significant increase in the risk of developing radiographic symptomatic hip OA in women and men ranging from a factor of 2 to 4.5, respectively (37,40,41). In contrast, several surveys have found no increased risk for the development of hip OA secondary to running or increased physical activity levels (42)(43)(44)(45).…”
mentioning
confidence: 85%
“…Prolonged exposure to higher levels of recreational physical activity has been reported to have a statistically significant increase in the risk of developing radiographic symptomatic hip OA in women and men ranging from a factor of 2 to 4.5, respectively (37,40,41). In contrast, several surveys have found no increased risk for the development of hip OA secondary to running or increased physical activity levels (42)(43)(44)(45).…”
mentioning
confidence: 85%
“…Mo st studies of top athletes and sportsmen have found no increase in the occurrence of osteoarthritis of the hip (6)(7)(8)(9) . These findings agree with our own findings and suggest that sport is unlikely to contribute greatly to the burden of disease in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of patients with asymmetrical paralysis of the lower limbs following poliomyelitis showed a lower prevalence of hip osteoarthritis on the weaker side (3). But examinations of runners and ballplayers who stress their hips in the course of their sport have produced conflicting findings, some studies indicating high rates of osteoarthritis (4)(5) and others no such increased risk (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The same observation has been made of professional soccer players and long distance runners (4,45,51). On the other hand the occurrence of osteoarthritis in the knees of reinforced concrete workers was relatively high (38 Ofo) (67).…”
Section: (5%)mentioning
confidence: 60%